Accuracy of a single measurement site for self-monitoring of patients with breast cancer at risk for lymphedema. (2nd December 2019) - Hidding, Janine T.; Beurskens, Carien H.G.; De Vries, Marijke T.; Nijhuis-van der Sanden, Maria W.G.; van Laarhoven, Hanneke W.M.; van der Wees, Philip J.
ABSTRACT: Purpose : Early detection of breast cancer-related lymphedema through simple self-monitoring techniques may lead to early treatment and improved outcomes. Methods : Prospective study of circumference measurements at four time points before, during, and after adjuvant chemotherapy with docetaxel, doxorubicin, and cyclophosphamide. Volume was calculated using the 10-cm interval circumference measurement method (reference test) and percentage difference between arms, for volume and circumference, was determined. First, the most valid single measurement location was determined by calculating Pearson's correlation coefficient relative to the reference test. Second, to evaluate the responsiveness to change over four time points, outcomes of the selected single measurement and the reference test were analyzed by repeated-measures ANOVA. Third, area under the curve (AUC) was used to determine the optimal sensitivity and specificity of the selected single measurement site (index test). Relationship between lymphedema (yes/no) and heaviness and swelling (yes/no) was analyzed using phi-coefficient. Results : The measurement point 30 cm proximal to the styloid process showed the highest correlation with percentage difference in total arm volume ( r  = 0.80) and detected increased percentage difference between arms after treatment. Analyses showed high accuracy (AUC = 0.94; 95% CI 0.90–0.99) and good sensitivity (0.85) and specificity (0.85) using a cutoff score of 4% circumference difference between arms at this location. A moderate correlation between feelings of heaviness and swelling to lymphedema was observed ( r φ  = 0.64). Conclusions : Circumference difference between arms of 4% measured at 30 cm proximal to the styloid process can be used as a surveillance site for further monitoring of patients at risk for lymphedema and may contribute to early diagnosis. Feelings of heaviness or swelling have moderate relationship with lymphedema, which needs to be confirmed in clinical practice.